Publicidad y traducción: el robo de mitos y contramitos en un mundo globalizado - Calzada Pérez, María (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Advertising is an essential component of a new form of postcolonialism – globalization (and its associated partner consumerism). Some form of critical resistance seems necessary. Supporting the ‘translation turn’ (Bassnett 1998), the present paper wishes to underline the significance of translation studies for the analysis of textual rewritings in order to analyse textual rewritings (ads in this case). Drawing on Vidal Claramonte (1998) and semiotics (Barthes in particular), it discusses the notions of denotation, con¬notation, myth and countermyth and applies them to the study of three original and translated/translatable printed ads.